STRATEGI PARTAI PERSATUAN PEMBANGUNAN (PPP) DALAM MEMOBILISASI PEMILIH PEREMPUAN DI JAWA BARAT (Analisis Modal Sosial Pierre Bordieu) - Fujilestari, Noer Apptika; Aprimayanti, Risyah (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study examines the political strategy of the United Development Party (PPP) in mobilizing female voters in West Java during the 2024 Legislative Election. The research applies Pierre Bourdieu’s theory of social and cultural capital combined with contemporary political strategy and political marketing frameworks. Using a qualitative case study approach, data were collected through in-depth interviews, party documents, and campaign materials. The findings demonstrate that PPP integrates women not merely as quota fulfillment but as central actors in electoral mobilization through pesantren networks, religious communities, women’s wings organizations, and digital platforms. The party implements offensive expansion strategies, defensive ideological consolidation, and adaptive digital communication strategies. This study contributes to the literature on Islamic political parties, gender representation, and local democracy in Indonesia.